Leadership dimensions influencing sustainability leadership in Sri Lanka: Mediating effect of manager’s sustainable thinking and organizational change - Sumanasiri, E.A.G. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This study examines the mediation effect of sustainable thinking and organizational change on the leadership dimensions that influence sustainability leadership among Sri Lankan managers. Sri Lanka is a developing country with strong social-cultural values that promote sustainability. The responses of 821 managers were analysed using factor analysis and structural equation modeling. The findings confirm that stakeholder relations are the most influential dimension for creating sustainability leadership. Mediation analysis tests confirmed that the two mediators of sustainable thinking and change leadership fully mediate the relationships between employee engagement and the leader’s concern for social and environmental sustainability, which concern was identified as the weakest of the three leadership dimensions, suggesting that long-term orientation has less potential for creating sustainability leadership among Sri Lankan managers.
Keywords: Sustainability leadership, leadership behaviours, cultural modeling and developing economies, Sri Lanka